Dog Man a tale of two kitties - Pilkey, Dav 1966-; Garibaldi, Jose (New York, NY Graphix, an imprint of Scholastic, 2017)
"Canine cop Dog Man is back, and he's about to be bested by the world's most conniving cat crook!"--
At head of title: Tree-House Comix proudly presents
Comic strips
1
Keywords: Cats -- Fiction; Dogs -- Fiction; Graphic novels; Humorous stories; Police -- Fiction; Graphic novels